Sistem Informasi Penjadwalan Maintenance Menggunakan Metode Watefall Berbasis Desktop Pt.Pindodeli 2 Pulp And Mills - Restu Nugraha; Asep Erik Nugraha; Rizki Achmad Darajatun (Peneliti.net, 2022)
In this era of globalization, machine maintenance management is an important aspect that determines the success and sustainability of a manufacturing industry. The development of information technology provides new opportunities for improving the performance of care management. Data management with the help of information systems will increase the effectiveness and efficiency of machine maintenance management activities every company needs fast information. So far, to monitor asset data in the form of computer goods, it still uses MS. Office (Excel) or manuals for data processing. The maintenance division is required to record and monitor each requested machine. The purpose of the research conducted is to design a well-integrated maintenance scheduling information system. In this study, an information system application was made using the Waterfall method which will facilitate the maintenance division in machine maintenance activities. The design of the information system is carried out until the stage of system development in the form of an information system program application. The information system application consists of a dabase system program that uses Visual Basic.Net, MySql. This machine maintenance information system is expected to be able to support the planning process of maintenance activities and make the repair process more effective, so as to increase machine productivity